Microbial load, cholesterol levels and sensory quality of hard-boiled commercial eggs (1999)
Microbial flora and load, Cholesterol levels and sensory quality of attributes of hard-boiled commercial eggs being hawked along Lagos-Ilorin Road were monitored in this study. The bacteria isolated from the eggs include; Achromobacter sp. and Staphylococcous aureus. While the eggs sampled from Ibadan, Ogbomoso and Ilorin had lower microbial load (20 - 33 X 10(4) CFU/g). On the average a 56g egg was found to contain 235mg Cholesterol. The results of sensory quality evaluation showed that the panelists that rated the eggs for appearance of albumen, and yolk, juiciness, flavour, firmness and Overall acceptability preferred and rated higher eggs obtained from Ibadan, Ogbomoso and Ilorin when compared with eggs obtained from Lagos and Oyo States. The implications of these findings from the standpoint of food poisoning and public health were discussed.